Comparison of laparoscopic excision versus open transvesical excision for symptomatic prostatic utricle in children - Jia, Wei; Liu, Guo-chang; Zhang, Li-yu; Wen, Ying-quan; Fu, Wen; Hu, Jin-hua; Xia, Hui-min (Journal of pediatric surgery, 2016)
The aims of this study were to report our clinical experience with laparoscopic excision (LE) and to compare the outcomes of LE versus open transvesical excision (OTE) for the management of prostatic utricle (PU) in children. This was a retrospective single-center study of 14 children who underwent OTE or LE for managing symptomatic PU between April 2003 and December 2014. Age, utricle size, operative time, estimated blood loss, duration of hospital stay, indwelling time of the urethral catheter, presence of residual postoperative utricular stump, and complications were compared between the two groups. There were no significant differences in age or utricle size between the two groups. Compared to the OTE group, the LE group experienced shorter operative times, lower estimated blood losses, and shorter hospital stays. Indwelling time of the urethral catheter was nearly 8days in the OTE group and 6days in the LE group. All patients had a follow-up visit between 6months and 2years after surgery. Two patients in the OTE group had transient UTI. Postoperative VCUG showed minimal residual utricular stump for 3 patients in the OTE group. However, no patient in either group required further operative therapy. LE is a safe and feasible procedure for symptomatic PU in children. Compared to OTE, LE can provide minimally invasive access for achieving good exposure with good short-term outcomes.